Major Aortopulmonary Collateral Arteries and Their Effects on Perioperative Parameters and Mortality of Children with Tetralogy of Fallot: A Case-control Study - Mohammadreza Edraki; Amir Naghshzan; Hamid Amoozgar; Kambiz Keshavarz; Nima Mehdizadegan; Hamid Mohammadi (Iranian Journal of Medical Sciences)
Background: Inadequate pulmonary blood flow in tetralogy of Fallot (TOF) can lead to the development of major aortopulmonary collateral arteries (MAPCA), which interferes with surgical repair. The present study evaluated the features of MAPCAs among patients with TOF and their treatment approaches. Besides, perioperative parameters and mortality rates of our TOF patients with and without MAPCA were compared. Methods: This retrospective case-control study was conducted from 2011 to 2020 at Namazi and Shahid Faghihi Hospitals, affiliated with Shiraz University of Medical Sciences, Shiraz, Iran. The significant aspects of MAPCAs, including their quantity, the presence of dual or single supply lung segments, and the employed devices for closure were evaluated. The patients were divided into three groups: TOF patients without MAPCAs as the control group, those with preoperative percutaneous MAPCA closure (Closed MAPCA), and those with small MAPCAs deemed unsuitable for percutaneous closure (Open MAPCA). A comparative analysis, encompassing hospital and surgical data, such as the presence of MAPCA, blood transfusion volume, intubation time, ICU stay, and mortality rates during and post-surgery, was performed among the aforementioned groups. The Chi square, Mann-Whitney, and Kruskal-Wallis tests were used to analyze the data.Results: 59 patients were enrolled, with a mean age of 27.98±24.19 months. The control group included 34 patients with no collaterals, the closed MAPCA group had 12 patients with occluded collaterals, and the open MAPCA group had 13 patients with small collaterals unsuitable for closure. Blood transfusion volume and intensive care unit (ICU) stay were significantly higher in the open MAPCA group than the control group (P=0.01 and P=0.04, respectively). The highest mortality rate was seen in the Iranian Journal of Medical Sciences group (P<0.001). Conclusion: In TOF patients, percutaneous MAPCA closure prior to surgical repair was recommended. This approach could potentially decrease the occurrence of complications both during and post-surgery.